2017
DOI: 10.3897/phytokeys.81.13488
|View full text |Cite
|
Sign up to set email alerts
|

Five new species of Syzygium (Myrtaceae) from Sulawesi, Indonesia

Abstract: Following ongoing ecological research on the tree diversity of the Indonesian island of Sulawesi, we describe five new species of Syzygium. These are the first descriptions of Syzygium species from the island since Blume (1850, Jambosa celebica and J. cornifolia), highlighting the significant lack of taxonomic research on the genus for the region. The five species proposed as new are Syzygium balgooyi sp. nov., Syzygium contiguum sp. nov., Syzygium devogelii sp. nov., Syzygium eymae sp. nov., and Syzygium gala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Morphological observation of several sterile specimens in BO collected by Brambach et al 0176,0206,0283,0319,0332,0466 & Culmsee 125, were firstly identified by Brambach et al (2017) as Syzygium balgooyi, indicate that its do not seem to get into the species. Small tree up to 7 m tall.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Morphological observation of several sterile specimens in BO collected by Brambach et al 0176,0206,0283,0319,0332,0466 & Culmsee 125, were firstly identified by Brambach et al (2017) as Syzygium balgooyi, indicate that its do not seem to get into the species. Small tree up to 7 m tall.…”
Section: Resultsmentioning
confidence: 99%
“…After viewing the specimens and also studying the publication of Brambach et al (2017), Schumann & Hollrung (1889) and Haron et al (1995) it appears that from the leaf morphology, the species is easier to distinguish from S. balgooyi and S. schumannianum especially in petiole, leaf base, leaf shape and size, also intramarginal nerve. While the latter two species are rather difficult to distinguish.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations